2022
DOI: 10.1038/s41590-021-01104-y
|View full text |Cite
|
Sign up to set email alerts
|

Pathological sequelae of long-haul COVID

Abstract: an estimated 254 million cases and 5.1 million deaths have been ascribed to COVID-19 1 . As the world grapples with successive waves of infection fueled by the emergence of viral variants, in a subset of patients who recover, protracted disease symptoms, termed 'long COVID' , 'long-haul COVID' or 'post-COVID syndrome' , are being increasingly recognized. In the absence of a unifying disease definition, working constructs of long COVID have included the persistence of a constellation of symptoms for time period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
433
2
14

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 505 publications
(526 citation statements)
references
References 115 publications
6
433
2
14
Order By: Relevance
“…The PCS found to be most prevalent in our study have also been reported by previous studies done in different parts of the world (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), although the relative distribution varied among cohorts, as did the demographic and clinical associations. The most extensive and long physical follow-up study, done in Wuhan, China, reported fatigue and muscle weakness (63%) and sleep difficulties (26%) to be the most prevalent PCS at a median of 186 days since symptom onset (N=1655) (9).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The PCS found to be most prevalent in our study have also been reported by previous studies done in different parts of the world (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), although the relative distribution varied among cohorts, as did the demographic and clinical associations. The most extensive and long physical follow-up study, done in Wuhan, China, reported fatigue and muscle weakness (63%) and sleep difficulties (26%) to be the most prevalent PCS at a median of 186 days since symptom onset (N=1655) (9).…”
Section: Discussionsupporting
confidence: 90%
“…A major concern amidst this pandemic has been the long term morbidities in the individuals recovering from COVID-19 disease, the so-called 'long COVID' (6,7). The 'long-haul COVID', which has emerged as a definite clinical entity all over the world, has largely been attributed to the undue lingering of the systemic inflammation for variable time periods (8). Exploring the factors that make convalescent subjects more susceptible to long-COVID is a domain of active research.…”
Section: Introductionmentioning
confidence: 99%
“…The pathological consequences of ACE-2 independent infection remain to be characterized, and one might speculate that ACE-independent infection may play a role in long-COVID 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, CoVs and RSV replicate in the host cell’s cytosol, while flu replicates in the nucleus; however, all of these viruses are susceptible to probenecid. As viruses modify host genes and pathways to facilitate viral replication, it is possible that probenecid treatment may modify viral-mediated changes that contribute to the treatment of “long COVID” symptoms [ 73 , 74 ], where PANX1 expression in the brain and synaptic plasticity are modified by COVID [ 75 , 76 ].…”
Section: Probenecid and Inflammationmentioning
confidence: 99%